Radiological risk assessment of concrete building materials in Peninsular Malaysia - Aznan Fazli Ismail,; Amran Ab. Majid,; Muhamad Samudi Yasir,; Redzuwan Yahaya,; Ismail Bahari, (Universiti Kebangsaan Malaysia, 2010)
The use of building materials containing high concentration of naturally occurring radioactive material (NORM) may result in the increase of radiation dose rate inside the building. The assessment of radiological hazard in building materials is necessary due to the concern of radiological impact to its dwellers. Thus, the objectives of this study were to determine the level of natural radioactivity in Malaysia’s building materials and to assess the associated radiological risk among dwellers. A total of 46 sands, 43 gravels and 13 Portland cement samples have been analysed using a gamma spectrometry system. Activity concentrations of 226Ra, 232Th and 40K were found to be in the range of 4.4 Bq kg-1 to 354.9 Bq kg-1, 2.4 Bq kg-1 to 263.9 Bq kg-1 and 15.1 Bq kg-1 to 1931.7 Bq kg-1, respectively. The indoor dose rates were found to be lower than 1500 μSv year-1, which is the recommended limit for building materials. A few samples were found to have high values of the representative gamma level index, external hazard index and internal hazard index compared to the suggested value of one. The radiological risk assessments to dwellers using Resrad-Build computer code showed that the dose rates for the Portland cement, sand and gravel increased annually over a period of 50 years.